Dog Man : Brawl of the wild - Pilkey, Dav, 1966-; Beard, George (Fictitious character); Hutchins, Harold (Fictitious character) (New York, NY : Graphix, an imprint of Scholastic, 2021)
"When Dog Man is sent to the pound for a crime he didn't commit, his friends work to prove his innocence"--OCLC.
2.6
3-6.
3-6
Keywords: Cats -- Comic books, strips, etc -- Juvenile fiction; Dogs -- Comic books, strips, etc -- Juvenile fiction; Humorous stories; Police -- Comic books, strips, etc -- Juvenile fiction; Cartoons and comics; Cats -- Fiction; Dogs -- Fiction; Humorous stories; Police -- Fiction; Cats -- Comic books, strips, etc -- Fiction; Dogs -- Comic books, strips, etc -- Fiction; Police -- Comic books, strips, etc -- Fiction; Funny animal comics; Graphic novels; Humorous comics